Steppe Eagle Population Structure Genetic Study: is There Hope for the Endangered Species? - Ludmila S. Zinevich; Dmitry M. Schepetov; Valentina G. Tambovceva; Rinur H. Bekmansurov; Genriyetta I. Pulikova; Elvira G. Nikolenko; Igor V. Karyakin (Пернатые хищники и их охрана)
For centuries, Steppe Eagle (Aquila nipalensis) had been the most numerous Palearctic Aquila species, but nowadays it has been decreasing in numbers progressively, so in 2015 the IUCN changed the species status to “endangered”. The decrease is evidently related to Steppe Eagles’ electrocution at nesting areas and during migration, poisoning by veterinarian drugs feeding on agricultural animal carcasses at wintering grounds, steppe fires and total habitat loss combined with loss of prey like susliks. To the contrary, the sister Aquila species, the Imperial Eagle (Aquila heliaca) which exhibits similar biological traits and lives simpatrically to the Steppe Eagle at some parts of areas, shows local increase in numbers and even substitutes the decreasing Steppe Eagle in steppe biomes. In 1960s, many Palearctic birds of prey came through population decline due to so-called «DDT crisis» – massive pesticide poisoning. To restore the species numbers, specific conservation actions were initiated in Europe to support population numbers and genetic diversity of raptors.